Efecto de solvente sobre la descomposición térmica de trans-3,6-dimetil-3,6-difenil-1,2,4,5-tetraoxaciclohexano en solución - Eyler, Gladys Nora (2004)
The thermal decomposition reaction of trans-3,6-dimethyl-3,6-diphenyl-1,2,4,5tetraoxacyclohexane (acetophenone cyclic diperoxide, DPAF), in different solvents (methanol, 1,4-dioxane, acetonitrile and 2propanol/benzene mixtures) in the initial concentration and temperature ranges of (4.2-10.5) x 10 M and 140.0 to 185.0 ºC, respectively, follows a pseudo first order kinetic law up to at least 70% DPAF conversion. An important solvent effect on the rate constant values, activation parameters (DH and S) and reaction products obtained in different solvents is detected, showing that the reaction is accelerated in alcohols.